2018
DOI: 10.3390/molecules23112745
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Quantification of Flavanol Glycosides in Vitis vinifera Grape Seeds and Skins during Ripening

Abstract: Monomeric and dimeric flavanol glycosides were analyzed in Vitis vinifera grapes and seeds during ripening. An analytical method using ultra-high performance liquid chromatography coupled with a triple quadrupole mass spectrometry (UHPLC-ESI-QQQ-MS/MS) in multiple reaction monitoring (MRM) mode was employed. Three grape varieties (Merlot, Syrah and Tannat) were chosen and grape berries were sampled at different stages of development. Ten monoglycosylated and six diglycosylated flavanol monomers were detected. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 36 publications
3
14
0
Order By: Relevance
“…This study reports the kinetics of extraction of monomeric and dimeric flavanols of mono- and diglycosides in GRE and SYR grape berries, and for the first time, in wine during fermentation. Data were obtained for a total of 22 isomers using a new UHPL-MS technique described in previous work [21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study reports the kinetics of extraction of monomeric and dimeric flavanols of mono- and diglycosides in GRE and SYR grape berries, and for the first time, in wine during fermentation. Data were obtained for a total of 22 isomers using a new UHPL-MS technique described in previous work [21].…”
Section: Discussionmentioning
confidence: 99%
“…(+)-catechin was purchased from Sigma Chemical Company (St Louis, MO, USA). The (+)-catechin 4′- O -β-glucoside (C4′OG) was hemi-synthesized as described previously [21].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Flavanols are bioactive secondary metabolites found in skins and seeds and can be found as monomers, polymers, or as glycosylated hexoside forms (Pérez-Navarro, Cazals, et al, 2019;Popov, Hejtmánková, Kotíková, Střalková, & Lachman, 2017;Zerbib, Cazals, & Enjalbal, 2018). Pérez-Navarro, Cazals, et al (2019) studied the flavanol glycoside profiles of three white (Airén, Albillo Dorado, and Montonera del Casar) and three red (Moribel, Tempranillo, and Tinto Fragoso) grape seeds and peels and revealed Abbreviations: GAE, gallic acid equivalents; TAE, tannic acid equivalents; TE, trolox equivalents; IC 50 , DPPH inhibition percent; TEAC, trolox equivalent antioxidant capacity; ORAC, oxygen radical absorbance capacity; ND, not determined; LD, detection limit.…”
Section: Polyphenolic Profile Of Grape Byproductsmentioning
confidence: 99%
“…Higher monomeric flavanol diglycosides amounts were found in seeds, whereas monoglycosylated dimmers were identified only in peels. Greater quantities of glycosylated flavanols were found in red varieties compared to the white ones, suggesting the dependence of flavanol glycoside profiles on the variety, grape maturity, and environmental conditions (Pérez-Navarro, Cazals, et al, 2019;Zerbib et al, 2018). The particle size of grape byproducts also influences the phenolic content as Beres et al (2016) and Zhao et al (2015) showed.…”
Section: Polyphenolic Profile Of Grape Byproductsmentioning
confidence: 99%